Staining of Frozen and Formalin‐Fixed, Paraffin‐Embedded Tissues with Metal‐Labeled Antibodies for Imaging Mass Cytometry Analysis. Issue 1 (13th February 2018) - Chang, Qing; Ornatsky, Olga; Hedley, David
Abstract: This unit describes protocols for labeling tissue sections using combinations of metal‐tagged antibodies and an iridium‐containing DNA intercalator for analysis by imaging mass cytometry. Imaging mass cytometry (IMC) allows the labeling of up to 40 individual markers simultaneously using antibody cocktails. We discuss labeling of both cryostat sections and sections from formalin‐fixed, paraffin‐embedded (FFPE) tissue blocks. The protocols are similar to those used for optical microscopy techniques, while allowing much higher complexity of analysis. © 2017 by John Wiley & Sons, Inc.